2018
DOI: 10.1016/j.cub.2018.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making through Integration of Sensory Evidence at Prolonged Timescales

Abstract: In Brief Waskom and Kiani quantitatively evaluate human decision-making behavior using a new psychophysical task that extends deliberation times to previously untested durations. They show that sensory-guided choice reflects linear integration of evidence with minimal loss of information over time, violating predictions from many biophysical models.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 57 publications
(76 reference statements)
8
34
3
Order By: Relevance
“…But neither our experiment nor our analysis presumes a drift diffusion model, or that evidence is being accumulated, in either species. The data presented here are consistent with evidence accumulation, but we have not done other tests, such as motion kernel analysis (8) or choice prediction from reaction time (31), to distinguish integration from other strategies, such as extrema detection (32).…”
Section: Discussionsupporting
confidence: 79%
“…But neither our experiment nor our analysis presumes a drift diffusion model, or that evidence is being accumulated, in either species. The data presented here are consistent with evidence accumulation, but we have not done other tests, such as motion kernel analysis (8) or choice prediction from reaction time (31), to distinguish integration from other strategies, such as extrema detection (32).…”
Section: Discussionsupporting
confidence: 79%
“…experiment 4). Such stimulus-locked temporal sensitivity is frequently observed in perceptual decision making paradigms and in part may reflect the participant-specific strategies for analyzing the sensory environment, temporal leakage in decision processes, or the urgency to respond [44,45]. Importantly, our results show that this sensitivity profile is augmented by a more rapidly changing temporal structure that emerges at precisely those time scales deemed relevant for auditory perceptual sensitivity by neuroimaging studies.…”
Section: Discussionsupporting
confidence: 50%
“…Recent work has suggested that when traditional evidence accumulation tasks are performed, it is hard to dissociate whether subjects are combining information across samples, or whether conventional analyses may be disguising a simpler heuristic 32,33 . In particular, an alternative decisionmaking strategy which does not involve temporal accumulation of evidence is to detect the single most extreme sample.…”
Section: Resultsmentioning
confidence: 99%